The Fundamental Issue in Tugendhat’s Critique of Heidegger: Falsehood, Disclosure, and the Semantic Transition of ‘Truth’ - Taddei, Paulo Mendes (2020)
The objections made by Daniel Dahlstrom (2001) and by Rufus Duits (2007) against Tugendhat’s criticism of Heidegger’s concept of truth are reconstructed in this paper. Both purport to defend Heidegger against Tugendhat’s charges by showing that the most primordial concept of truth as unconcealment (Unverborgenheit) does account for falsehood. Roughly while Dahlstrom maintains that Tugendhat does not does justice to the transcendental character of Heidegger’s primordial truth, Duits contends that Tugendhat is still attached to the metaphysical perspective of Vorhandenheit. The aim of this paper is to show that both contenders miss the decisive point in Tugendhat’s critique, which lies, as part of the literature has shown (LAFONT, 1994; SMITH, 2007), not so much in the demand for an explanation of falsehood, but rather in the demand for a justification for the semantic transition of ‘truth’. After showing in the first two sections how respectively Dahlstrom and Duits miss the core of Tugendhat’s criticism, I defend in the third section my interpretation of Tugendhat’s critique against certain reservations recently articulated by Wrathall (2011). I conclude by both pointing out the alignment between my proposal and Heidegger’s own concession in Das Ende der Philosophie und die Aufgabe des Denkens and indicating some pending issues.